2013
DOI: 10.3892/ijo.2013.2049
|View full text |Cite
|
Sign up to set email alerts
|

Cancer upregulated gene 2, a novel oncogene, enhances migration and drug resistance of colon cancer cells via STAT1 activation

Abstract: Abstract. Cancer upregulated gene (CUG) 2, as a novel oncogene, has been predominantly detected in various cancer tissues, such as ovary, liver, lung and colon. We recently showed that CUG2 elevates STAT1 activity, leading to resistance to infection by oncolytic vesicular stomatitis virus. To investigate a possible role for CUG2-induced activation of STAT1 in oncogenesis, we first established a colon cancer cell line stably expressing CUG2 (Colon26L5-CUG2). Colon26L5-CUG2 exhibited higher levels not only in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…AKT activation can inhibit apoptosis (44), and we speculate that this mechanism may be responsible for the inhibition of apoptosis observed in BCCLs upon IL15 stimulation. JAK1/STAT1 signaling is known to play a role in cell motility (45,33). This is consistent with our observation of impaired migration of IL15RA/IL15-expressing cells upon JAK1 knockdown in the absence of any significant reduction in growth rate.…”
Section: Discussionsupporting
confidence: 81%
“…AKT activation can inhibit apoptosis (44), and we speculate that this mechanism may be responsible for the inhibition of apoptosis observed in BCCLs upon IL15 stimulation. JAK1/STAT1 signaling is known to play a role in cell motility (45,33). This is consistent with our observation of impaired migration of IL15RA/IL15-expressing cells upon JAK1 knockdown in the absence of any significant reduction in growth rate.…”
Section: Discussionsupporting
confidence: 81%
“…Some recent studies identified novel targets to improve VSV-mediated oncotoxicity. A novel oncogene was recently found, named cancer upregulated gene 2 (CUG2), which activates Ras and mitogen-activated protein kinases (MAPKs), including ERK, JNK and p38 MAPK [91]. CUG2 was shown to confer resistance to VSV through STAT1-OASL2 signalling [92].…”
Section: Increasing Direct Oncotoxicitymentioning
confidence: 99%
“…STAT1 has been classically defined as a Th1 proimmune and antitumor transcription factor, based on its canonical role in IFNg signaling and on studies using STAT1 À/À tumor cells and regulate DNA repair pathways and to be upregulated in several late-stage human cancers, including those of the breast, colon, glioblastoma, and soft tissue sarcoma (13)(14)(15)(16). Overexpression of the IFN-STAT1 pathway is also associated with poor prognosis in different types of cancer (17)(18)(19)(20), especially in breast cancers in which increased IFN-STAT1 pathway activity is considered a marker predicting resistance to chemotherapy and radiotherapy (17,21).…”
Section: Introductionmentioning
confidence: 99%